(untitled) (Journal of Pathology of Nepal, 2015)
Background: Morphological examination of the marrow requires a combination of a properly prepared bone marrow aspirate smear, a trephine biopsy section and an imprint of core biopsy. Some conditions often result in a dry tap and are best studied by marrow biopsy.The major drawbacks of biopsy sections are their thickness, precludingfine morphologic detail.The objective of this study was to compare the diagnostic accuracy, cellularity and cytomorphology from bone marrow biopsy core imprint smears with bone marrow aspiration smears. Materials and Methods: Imprint smears were prepared from 138 cases subjected to bone marrow examination. The bone marrow aspiration, imprint smears andbone marrow biopsy sections were examined and were categorized into five different groups on cytomorphological basis: Non-malignant alterations and normal marrow, Myeloid neoplasms, Plasma cell myeloma, myelo-infiltrative disease and absence of residual disease and further delineated into specific entities wherever necessary. Results: Out of 138 cases, non-malignant alterations and normal marrow was the largest subgroup (N=87, 63%), followed by myeloid neoplasms (N=26, 18.5%), Plasma cell myeloma (N=13, 9.4%), myelo-infiltrative disease (N=9, 6.5%) and absence of residual disease (N=3, 2.2%). The diagnostic accuracy of imprint smears was highest (92%) followed by biopsy sections (89.9%) and aspiration smears (87%). Kappa analysis showed strong agreement (>0.8) and p-value was statistically significant (<0.001) while correlating the final diagnosis. Conclusion: Imprint smear technique is a simple, rapid, inexpensive and reliable procedure. The routine use of imprint smear in the bone marrow examination will serve as an invaluable adjunct to bone marrow aspiration and biopsy. Journal of Pathology of Nepal (2015) Vol. 5, 739-746